Estudo do comportamento físico da hidroxiapatita dopada com ferro - Pinto Filho, Francisco (2008)
The bioceramic called hydroxyapatite (HA) is a biocompatible material which can be an important tool in hyperthermia applications for the treatment of bony cancer. In this work the effect of the addition of Fe ions in the structure of the HA was investigated with the objective of obtaining a magnetic bioceramic to be used in the hyperthermic treatment against the cancer. The samples were prepared by the ceramic method and characterized by the X-ray diffraction (XRD), infrared spectroscopy (FTIR), Vickers hardness, electric properties (constant and loss dielectric) and scanning electronic microscopy (SEM). The presence of the phase Ca2Fe2O5 was verified by X-ray diffraction analysis, showing a structure Brownmillerite. The improvement of the mechanical and electric properties was verified with the increase of the sintering temperature. It was observed that the increase of the Fe addition and the sintering temperature caused morphologic changes in the grains.